Смерть Катона: роман / Игорь Николенко - Николенко Игорь Алексеевич (Современник, 1990)
Экземпляры: ф. 1 (20090226) / Инвентарный номер: 93803 / Цена: 10.00 / Авт.знак: Н 63 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6